Soil organic carbon and nutrient content across agricultural systems in the forest-savannah transition zone of Cameroon - Mandah, V.P.; Masso, C.; Onana, A.A.; Fiaboe, K.; Arthur, E.; Giweta, M.; Ndango, R.; Silatsa, F.B.T.; Voulemo, D.D.I.; Biloa, J.B.; Ngeumezi, C.; Tematio, P. (Elsevier, 2025)
Accurate knowledge of soil characteristics is indispensable for large-scale agriculture while ensuring sustainability, climate change adaptation, and mitigation, which is lacking in Cameroon. This study aimed to assess soil organic carbon (SOC) and nutrient (NPK) content across agricultural systems in the forest-savannah transition zone of Cameroon. Seven agricultural systems were identified namely: the forest-based cocoa agroforestry (Fcocoa), savannah-based cocoa agroforestry (Scocoa), transition zone-based cocoa agroforestry (Tcocoa), savannah mixed cropping of yam, pumpkin, and maize (Sypm), savannah mixed cropping of groundnut, cassava and maize (Sgcm), transition zone mixed cropping of yam, pumpkin, and maize (Typm), and the transition zone mixed cropping of groundnut, cassava, and maize (Tgcm). The soil was sampled at two depths, 0–10 cm (upper layer) and 10–30 cm (lower layer) in three replicates for each farming system and analyzed. Significant differences appeared in soil organic carbon (SOC) (p < 0.002), Total nitrogen (N) (p < 0.001), C:N ratio (p < 0.002), pH (p < 0.01), bulk density (Bd) (p < 0.03), soil organic carbon stock (SOCS) (p < 0.001), and soil nitrogen stock (SNS) (p < 0.001). In the upper and lower layers, the highest concentrations of SOC (25.0 and 16.6 g kg−1), N (2.3 and 1.5 g kg−1), and P (5.1 and 3.3 g kg−1) were recorded in Fcocoa, and K (176.9 and 129.3 mg kg−1) in Scocoa respectively. In the croplands, soil nutrient content was higher in the transition zone while savannah croplands showed higher Bd (≥ 1.4 g cm−3). Soil nutrient content decreased from upper to lower soil layers with a significant difference (p < 0.05) in the croplands for pH, SOCS, and SNS, with a higher magnitude (p < 0.01) in Sgcm. Thus, agroforestry can be considered a potential solution towards ecological resilience.